Media Pembelajaran Instalasi Listrik Rumah Sederhana Untuk Pembelajaran Instalasi Listrik - Saputra, Bagas Mei; Asni Tafrikhatin; Ajeng Tiara Wulandari (Politeknik Piksi Ganesha Indonesia, 2022)
The problem faced in learning at the Piksi Ganesha Indonesia Polytechnic, especially in engineering courses related to electricity on competency standards for installing simple electrical installations, is that there is no teaching media at the Piksi Ganesha Indonesia Polytechnic itself, especially in the Electronics Engineering Study Program. This learning media uses components: MCB, single switch, series switch, hotel switch, light fittings, lamps, cables and other supporting components. This learning media has been tested in electrical installation class classes. The results of testing the scores of all respondents obtained 63.3% to 83.3% in the category